Influencing factors of children's fruit, vegetable and sugar-enriched food intake in a Finnish preschool setting – Preschool personnel's perceptions. (1st August 2016) - Ray, Carola; Määttä, Suvi; Lehto, Reetta; Roos, Gun; Roos, Eva
Abstract: Introduction: A large proportion of young children spend most of their weekdays at preschool in Western countries. In Finland, three meals are included in a full day at preschool. These meals have the potential to promote healthy eating. This study aimed to obtain the personnel's (preschool teachers, day-care nurses) views on the factors influencing children's fruit, vegetable, and sugar-enriched food intake at preschool. Study design: Four focus groups, in all 14 preschool personnel. Two researchers independently analysed the data using a socio-ecological framework. Results: At the child level, age, peers, and the child's personality were recognized as factors influencing the fruit and vegetable (FV) and sugar-enriched food intake. At the preschool level, both the physical and social environments were discussed thoroughly, whereas at the societal level, policies of the EU, the state, and the municipality were mentioned as factors that influence what children eat in preschool. The personnel also discussed the interactions between factors both between levels and within levels. Conclusions: In Finnish preschools, children's food intake is influenced on and within several levels of the socio-ecological model. The identification of the factors influencing food intake allows different methods of intervention at multiple levels to promote healthy eating behaviours in preschools.